Leading edge of micro-nano science and technology : selected peer reviewed papers from the 11th China International Nanoscience and Technology Symposium (CINST 2012), October 21-25, 2012, Kunming, China - China International Nanoscience And Technology Symposium (11th : 2012 : Kunming Shi, China); Cong, Hailin; Lu, Xing; Yu, Bing, editor (Zurich-Durnten : Trans Tech Publications, 2013)
Includes bibliographical references and index